A Hybrid MCDM Model for New Product Development: Applied on the Taiwanese LiFePO4 Industry. (22nd January 2015) - Chen, Wen-Chin; Wang, Li-Yi; Lin, Meng-Chen
Abstract : Recent years, since problems with respect to atmosphere pollution hasten countries to accentuate green-related policy regarding the sustainable energy, the lithium-iron phosphate (LiFePO4 ) battery has been appealed to the world. However, more and more firms invest the LiFePO4 batteries production that has launched a fierce competition. Successful new product development (NPD) processes have been considered the key for LiFePO4 battery firms to increase their competitive advantage. Firms must make correct decision faster due to the rapid development of technology and the decreasing product life cycle. This study proposes a hybrid multiple criteria decision making (MCDM) model based on the literature review and consultation with the experts, interpretive structural modeling (ISM), and fuzzy analytic network process (FANP) for evaluating various strategies for NPD. First of all, reviewing of literature and meeting with the experts are used to screen factors and select the criteria. Then, an ISM is managed to determine the feedback and interdependency of those factors in a network. Finally, a fuzzy theory is applied to resolve the linguistic hedges and an ANP is adopted to obtain the weights of all the factors. A case study is undertaken to validate the model in a Taiwanese company that provides professional packing and design for lithium-iron phosphate battery.